Downregulation of miR-146b-3p Inhibits Proliferation and Migration and Modulates the Expression and Location of Sodium/Iodide Symporter in Dedifferentiated Thyroid Cancer by Potentially Targeting MUC20 - Hou, Shasha; Xie, Xiaorui; Zhao, Jing; Wu, Cailan; Li, Ning; Meng, Zhaowei; Cai, Chunquan; Tan, Jian (Frontiers in Oncology, 2021)
The dedifferentiation of differentiated thyroid cancer (DTC) is a challenging problem for radioactive iodine (131I) treatment, also known as radioiodine refractory differentiated thyroid cancer (RAIR-DTC). The purpose of this study was to further explore the mechanism of the redifferentiation of dedifferentiated thyroid cancer. Ineffective and effective groups of 131I therapy were analyzed and compared in both our clinical and TCGA samples. Whole-exome sequencing, mutation analysis, transcriptome analysis, and in vitro functional experiments were conducted. FLG, FRG1, MUC6, MUC20, and PRUNE2 were overlapping mutation genes between our clinical cases, and the TCGA cases only appeared in the ineffective group. The expression of miR-146b-3p target MUC20 was explored. The expression levels of miR-146b-3p and MUC20 were significantly increased, and the inhibition of miR-146b-3p expression significantly inhibited proliferation and migration, promoted apoptosis, regulated the expression and location of thyroid differentiation-related genes, and sodium/iodide symporter (NIS) in dedifferentiated thyroid cancer cells (WRO). Thus, miR-146b-3p potentially targets MUC20 participation in the formation of DTC dedifferentiation, resulting in resistance to 131I and the loss of the iodine uptake ability of DTC cancer foci, promoting refractory differentiated thyroid cancer. miR-146b-3p may be a potentially therapeutic target for the reapplication of 131I therapy in dedifferentiated thyroid cancer patients.